Pengembangan Model Perhitungan Saturasi Air (Sw) Untuk Pemodelan Saturation Height Function (SHF) Di Lapangan "MBES" - Efrata, Marojahan Benedict; Irawan, Dedy; Sinurat, Pahala Dominicus (Jurnal Jaring SainTek, 2025)
The determination of water saturation (Sw) is crucial in reservoir modeling as it significantly impacts hydrocarbon volumetrics calculations. Current methods such as Archie’s and Simandoux approaches often face challenges in capturing the complexities of heterogeneous reservoir rocks, particularly in carbonate formations. This study aims to develop an improved method for calculating Sw that enhances Saturation Height Function (SHF) modeling, especially in carbonate reservoirs, and can be validated with well log data. The proposed model offers a more accurate and efficient alternative by reducing the reliance on core permeability data and addressing the shortcomings of traditional methods. The research was conducted at the MBES field, located offshore in the Java Sea, Indonesia, focusing on the Talang Akar formation. The method integrates well log data and new computational techniques to predict water saturation in transition zones between oil, gas, and water. Results show significant improvements in the accuracy of SHF modeling, ultimately leading to more reliable predictions of hydrocarbon reserves and efficient reservoir management.